Energy and mobility in smart cities - Nuttall, William J.; Gibson, David V.; Trzmielak, Dariusz; Ibarra-Yunez, Alejandro (ICE Publishing, 2019)
With a particular emphasis on developments relating to energy and mobility, the book provides a far-reaching analysis of key drivers of innovation, exploring potential opportunities and challenges associated with the rise of digital infrastructure and smart cities technology. The book is divided into four parts. Part 1 covers the changing nature of communities in the digital age, while Part 2 looks at mobility in smart cities, including the development of autonomous smart vehicles, and key innovations in logistics and transport. Part 3 focuses on energy and covers electricity markets in transition economies as well as the role of renewable energy in future smart energy systems. Part 4, on governance, examines political issues shaping the smart future, and principles of sustainable development, inclusivity and transparency in smart city development.